Implementation of Food and Cash Assistance for Sustainable Welfare: A Sharia Economic Perspective in Eastern Gorom Ambon - Preti Nilam Wailissa; Muthoifin; Laylatushabrina Muharromah (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study explores the implementation of food and cash assistance programs aimed at improving sustainable community welfare from a Sharia economic perspective in Aran Village, East Gorom District, Eastern Seram Regency, Maluku Province. The objective is to critically examine the distribution process and assess the socio-economic impacts of these programs, particularly within the framework of Sustainable Development Goals (SDGs), specifically Goal 1 (No Poverty), and Goal 2 (Zero Hunger). Theoretical framework: The theoretical framework is grounded in concepts of social welfare, equitable distribution of social aid, and the Islamic economic principles of justice (‘adl) and mutual care (ta‘awun), emphasizing the government's role in alleviating poverty through inclusive and ethical means. Literature review: The literature review draws from prior studies on the effectiveness of social assistance schemes, challenges in beneficiary targeting, and the importance of synergy between central and local governments in ensuring program sustainability. Methods: This study employs a qualitative approach using in-depth interviews with key stakeholders, field observations, and secondary data analysis from government reports and institutional records. Data were gathered from various community actors, including aid recipients, local administrators, and program implementers. Results: Findings indicate that the distribution of basic food and cash assistance in Aran Village has been relatively well-executed, contributing to short-term relief and partial improvement in community welfare. However, significant challenges remain, including misidentification of eligible beneficiaries, limited budget allocations, logistical constraints due to geographic isolation, and weak inter-agency coordination. From a Sharia economic perspective, these inefficiencies contradict the ethical mandate to uphold justice and prioritize those most in need. Implications: The study concludes that enhancing transparency, refining verification mechanisms, and strengthening intergovernmental cooperation are crucial for achieving more effective, equitable, and sustainable aid delivery. Furthermore, integrating Islamic economic values into policy design can enhance the spiritual and ethical dimensions of poverty alleviation efforts in remote Muslim-majority areas. Novelty: The novelty of this research lies in its localized focus on a remote region rarely studied in academic literature and its incorporation of Sharia economic insights in analyzing the practical challenges of aid distribution within the SDGs context.